2011
DOI: 10.1007/s12034-011-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation behaviour of Sr 2 SbMnO 6 ceramics fabricated from nanocrystalline powders prepared by molten salt synthesis

Abstract: Double perovskite polycrystalline single phase and dense Sr 2 SbMnO 6 (SSM) ceramics, fabricated using the nanocrystalline powders synthesized by molten salt method, exhibited high dielectric constant with low dielectric loss as compared to that of SSM ceramics obtained from the powders prepared by solid-state synthesis method. The dielectric data obtained over a wide frequency (100 Hz-1 MHz) and temperature (190 K-300 K) ranges exhibited distinct relaxations owing to both the grain and grain boundary. The die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As can be seen from Table 2, the activation energy and correspondingly the time required for dielectric relaxation is higher for oxygen vacancy defects and thus the hopping from Fe 2+ /Fe 3+ . While the dielectric relaxation time for the composite is 10 times higher as compared to single phase Bi2Fe4O9, implying that the composite shows better capacitive effect and hence charge storage effects [27].…”
Section: Modulus Analysismentioning
confidence: 92%
“…As can be seen from Table 2, the activation energy and correspondingly the time required for dielectric relaxation is higher for oxygen vacancy defects and thus the hopping from Fe 2+ /Fe 3+ . While the dielectric relaxation time for the composite is 10 times higher as compared to single phase Bi2Fe4O9, implying that the composite shows better capacitive effect and hence charge storage effects [27].…”
Section: Modulus Analysismentioning
confidence: 92%
“…The Sr 2 MnSbO 6 perovskite is one compound of this type, and it has been synthetized via molten salt synthesis (MSS) method and convectional solid-state methods for example by (Cheah et al, 2006;Ivanov et al, 2009;Parada et al, 2018;Preethi-Meher et al, 2012). Experimental studies of Sr 2 MnSbO 6 have shown that this compound presents ferroelectric and ferromagnetic behavior in the I4m, I4mm, I4mcm phases, as well as it exhibits high dielectric constant in the cubic phase Fm-3m (Antara, et al, 2011;Foster, et al,1997;Majhi & Varma, 2007). Modifications of this compound recently have been reported by (Bazuev et al, 2021), where is studied the effect of substitutions on the phase formation, structure and magnetic properties of the Sr 2 MnSbO 6 compound.…”
Section: Physical Sciencesmentioning
confidence: 99%
“…10. 26 The equivalent circuit was tted by using EIS spectra analyser 1.0. 27 Due to the electrode polarization effect, we could not observe a full semi circular arc for all the temperatures.…”
Section: And 3 Respectivelymentioning
confidence: 99%